Social Inclusion as a Counter-Radicalism: A Study on Traditional Religious Institution in West Sumatra - Muliono (Universitas Wijaya Kusuma Surabaya, 2026)
This research explores social inclusion as a countering radicalism. The value of social inclusion stems from local community traditions, centered in the surau, and plays a vital role in fostering inclusive behavior. This study employs a qualitative approach, utilizing in-depth interviews and participant observation as data collection techniques. The results indicate that, first, West Sumatra is one of the regions susceptible to radicalism. Second, the traditional value system within surau religious practices serve as an effective medium to counter radicalism due to their inherently inclusive core values. Third, the values of social inclusion are manifested in the mamakiah tradition, which is cultivated among students (santri) within the surau. Surau is more than just a place of worship; it is a traditional religious educational institution and the central hub of the cultural system for the people of West Sumatra. The social inclusion found within the religious tradition of mamakiah underscores a significant value within the context of urban society. This study confirms that social inclusion stemming from local values serves not only as a preventive measure but also as a transformative approach to building moderate awareness. This is essential to counter radicalism, which has evolved alongside socio-political dynamics that have now permeated the field of education